Comparative efficacy of improved crop management technologies of wheat (Triticum aestivum) in Bihar - SINGH, A K; MALIK, R K; KUMAR, ANJANI; BURMAN, R ROY; ROY, PINAKI (The Indian Journal of Agricultural Sciences, 2019)
Wheat (Triticum aestivum L.) is the world’s most widely cultivated cereal crop. It is commonly eaten in both time meals in major wheat growing states. Field experiments were conducted at eight KVKs of Bihar during year 2016- 2018 based on different agro ecological situations. In the field experiment it was found that early wheat sowing has emerged as the most important variable for increasing the grain yield (5 t/ha) than late sown. Data shows that instead of skipping irrigation at grain filling stage, one irrigation applied at grain filling stage increased the wheat grain yield by 13% when the sowing was done with zero tillage and 16% when sowing was done by conventional method. With irrigation, the average grain yield of wheat with zero tillage was 5.30 t/ha compared to 4.54 t/ha under conventional tillage. To trace the impact of different herbicide application technologies, it was found multiple boom nozzle sfitted with flat fan nozzles and tractor mounted sprayer provided similar wheat grain yield (5.1-5.3 t/ha) than hollow cone nozzles with grain yield of 4.6 t/ha. It was referred that grain yield of wheat were 4.51, 4.60 and 4.38 t/ha following the application of glyphosate at 24, 48 h or 7-10 days before seeding wheat, respectively. Total 304 replications have been conducted to study the effect of ZT on the productivity of wheat sown at different times and was found that ZT wheat (HD-2967) planted from 1-15 November gives highest yield than other sowing date.